Preeclampsia – genes involved in inflammatory and vascular mechanisms - Díaz-Kuan, Alicia (2017)
This review describes the genes involved in the immune and angiogenic processes that lead to normal placenta development and vascularity. Any change in this fragile equilibrium may predispose to preeclampsia.